2002
DOI: 10.1097/00005344-200203000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Early Benefits of Pravastatin to Experimentally Induced Atherosclerosis

Abstract: There is little information regarding the time of hypolipidemic treatment of changes in atherosclerotic plaque, tissue cholesterol content, and also for the recovery of endothelial function. To assess the early effects of lipid-lowering treatment on these parameters, six groups of New Zealand male rabbits were studied. Animals in groups I and II were fed regular chow; groups III and IV received a 12-week 0.5% cholesterol diet followed by 12 weeks of 0.05% cholesterol diet. Finally, groups V and VI were fed a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…We previously demonstrated improved endothelial function by statins 25) and by angiotensin converting-enzyme inhibitor 26) , accompanied by attenuation of atherosclerosis development in rabbits, independent of changes in serum cholesterol levels.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 96%
“…We previously demonstrated improved endothelial function by statins 25) and by angiotensin converting-enzyme inhibitor 26) , accompanied by attenuation of atherosclerosis development in rabbits, independent of changes in serum cholesterol levels.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 96%
“…Pravastatin is a potent inhibitor of HMG-CoA reductase. Recently, a number of studies have demonstrated that pravastatin significantly inhibits the production of superoxide anions stimulated by phorbol ester in vascular endothelial cells [14] , suppresses the increase in oxidative stress induced by LPC in vascular smooth muscle cells [15] , and improves the impairment of endothelium-dependent relaxation in humans and animals with atherosclerosis and diabetes [16][17][18] . Therefore, it is important to determine whether pravastatin protects the vascular endothelium against damage due to LPC.…”
Section: Introductionmentioning
confidence: 99%
“…Blood from each rat was collected from carotid artery and then preparation of serum for estimation of lipid profile by enzymatic method and separation of erythrocyte and preparation of erythrocyte hemolysate for estimation erythrocyte malondialdehyde (MDA) 20 . The aorta was separated from the surrounding viscera, inner thoracic wall and abdominal wall and was dissected out to preserve for histopathological examination 21 . Morphological study of the aorta was done under microscope after preparation and staining of the aortic tissue slide 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Morphological study of the aorta was done under microscope after preparation and staining of the aortic tissue slide 22 . Intima-media ratio was measured by using Image-pro plus software 21 . All the quantitative data obtained from the experiments have been expressed as mean±standard deviation (mean±SD).…”
Section: Methodsmentioning
confidence: 99%